Poésie et dissidence à Cuba Engagement et désengagement des écrivains, de La Havane à Madrid (1966-2002) - Damerdji, Amina (Bibliothèque de la Casa de Velázquez, 2022)
In 1966, seven years after the advent of the Cuban revolution, a new poetic group was born around the magazine El caimán barbudo, affiliated to the Communist Party of Cuba. Their writing is turbulent, original, combining adherence to the regime and playful distance. The evolution of freedom of expression in Cuba and the national and international repercussions of their works, will push some of them on the path of exile and dissidence, others to find a singular way on the island. In 1996, a final attempt to reunite the group through the pages of the Madrid-based journal Encuentro de la cultura cubana redraws their ties. Combining literary studies and social sciences, this book traces the untold history of this group during the second half of the twentieth century and analyzes the way in which literature reinvents itself according to the political upheavals.